Strategi Efektif dalam Penggunaan Teknologi dan Edukasi untuk Pencegahan Diabetes Mellitus - Pujilestari, Intan; Monica, Rizqy Dimas; Rahayu , Ayu Hendrati; Ginting , Gerinata; Suharto, Suharto (PUAN INDONESIA, 2025)
Diabetes mellitus is a global health issue with increasing prevalence and serious complications that can affect the quality of life of those affected. Prevention is crucial to reduce the burden of this disease. Effective prevention strategies integrate technology and education for better outcomes. The use of technology, such as mobile health apps and glucose monitoring devices, provides easier and faster access for people to monitor their health. Health education delivered through various digital platforms, seminars, and campaigns increases awareness and understanding of diabetes risk factors and prevention steps. The integration of technology and education enables the delivery of more interactive and personalized information, encouraging the adoption of healthy lifestyles and stress management. However, challenges such as limited access to technology and varying levels of digital literacy require inclusive and adaptive approaches. Collaboration between government, private sector, and community organizations is key to supporting sustainable prevention programs. With the right strategies, diabetes mellitus prevention can be enhanced, reducing the risk of complications, improving individual quality of life, and lessening the economic burden on the healthcare system.